The phantom of the subway (New York : Scholastic, 2004)
When he hears reports of a ghost haunting New Mouse City's subway tunnels, Geronimo sets out to investigate the story.
"Original title: Il fantasma del metro"--T.p. verso.
RL3.
008-012.
edited hb 2015-06-16
Keywords: Animals -- Juvenile fiction; Humorous stories; Mice -- Juvenile fiction; Subways -- Juvenile fiction; Animals -- Fiction; Ghosts -- Fiction; Humorous stories. -- Fiction; Journalists -- Fiction; Mice -- Fiction; Mystery and detective stories. -- Fiction; Subways -- Fiction